1985
DOI: 10.1002/jpln.19851480307
|View full text |Cite
|
Sign up to set email alerts
|

Spatial variability of some nutrient constituents of an Alfisol from loess II. Geostatistical analysis

Abstract: Spatial variability of NO3, K, Mg and organic C of a loess field was studied by using a geostatistical concept, known as theory of regionalized variables. Fifty measurements were made at the nodes of a 30 m × 30 m grid for each of 0‐30, 30‐60 and 60‐90 cm depths. Semivariograms determined from the data showed that NO3 observations were spatially independent, and hence could be analyzed only by classical methods. Semivariograms of K, Mg and C showed these parameters to be correlated over space for a separating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0

Year Published

1988
1988
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 12 publications
1
14
0
Order By: Relevance
“…Also other authors observed lognormal N-NO 3¯ distributions (e.g. Meirvenne and Hofman 1989) but normal distribution was reported, too (Dahiya et al 1985, López-Granados et al 2002.…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…Also other authors observed lognormal N-NO 3¯ distributions (e.g. Meirvenne and Hofman 1989) but normal distribution was reported, too (Dahiya et al 1985, López-Granados et al 2002.…”
Section: Resultsmentioning
confidence: 93%
“…Ilsemann et al (2001) did not detect a range at three sites and they conclude that minimum distance between sampling positions was obviously too large to observe effects of small scale variability. Also Dahiya et al (1985) reported no spatial correlation of soil N-NO 3 . Meirvenne and Hofman (1989) observed ranges 9.5, 23 and 34 m for their data.…”
Section: Geostatistical Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…A comparison of the spatial variability of soil nutrients on two scales, 0.25 and 3.3 ha, showed that nitrate had the shortest range ( < 5 m) , soil organic carbon the longest (>180m), and phosphate an intermediate range (Cahn et al, 1994). In some studies, nitrate exhibited no spatial dependence for distances larger than the minimum sampling distance, which was 30 m in an Alfisol field for cereals and sugarbeet (Dahiya et al, 1985) or 0.4 m in grassland (White et al, 1987). Spatial variability of soil and crop parameters is influenced by time and by soil management.…”
mentioning
confidence: 99%
“…Differences in this characteristic were compared between individual plots, as well as within a plot; they were related to the possibility of exact identification of the plot and its parts and further usage of these data for specific measures, locally applied (Dahiya et al 1985, Brodský et al 2001, Baxter et al 2003.…”
mentioning
confidence: 99%